Electrode and electrolyte materials for electrochemical capacitors. (5th October 2017) - Mirzaeian, Mojtaba; Abbas, Qaisar; Ogwu, Abraham; Hall, Peter; Goldin, Mark; Mirzaeian, Marjan; Jirandehi, Hassan Fathinejad
Abstract: Among different electric energy storage technologies electrochemical capacitors are used for energy storage applications when high power delivery or uptake is needed. Their energy and power densities, durability and efficiency are influenced by electrode and electrolyte materials however due to a high cost/performance ratio; their widespread use in energy storage systems has not been attained yet. Thanks to their properties such as high surface area, controllable pore size, low electrical resistance, good polarizability and inertness; activated carbons derived from polymeric precursors are the most used electrode materials in electrochemical capacitors at present. Other electrode materials such as shaped nano-carbons or metal oxides are also investigated as electrode materials in electrochemical capacitors, but only as useful research tools. Most commercially used electrochemical capacitors employ organic electrolytes when offering concomitant high energy and high power densities. The use of aqueous based electrolytes in electrochemical capacitor applications is mainly limited to research purposes as a result of their narrow operating voltage. Recent studies on room temperature ionic liquids to be employed as electrolyte for electrochemical capacitor applications are focused on fine tuning their physical and transport properties in order to bring the energy density of the device closer to that of batteries without compromising the power densities. In this paper a performance analysis, recent progress and the direction of future developments of various types of materials used in the fabrication of electrodes for electrochemical capacitors are presented. The influence of different types of electrolytes on the performance of electrochemical capacitors such as their output voltage and energy/power densities is also discussed. Graphical abstract: Mechanism of charge storage and electron transfer in different capacitive devices (ESC: Electrostatic Capacitor; EDLC: Electric Double Layer Capacitor; PC: Pseudo- Capacitor). Highlights: The recent advances in the synthesis of electrode materials for ECs are presented. Improvements on the development of novel electrolytes for ECs are discussed. Relationship between adopted electrolytes with energy/power densities is analysed. Selection criteria and progress on the choice of binders for ECs are discussed. Impact of the optimization of electrode's porosity and electrolyte's type on the performance of ECs are examined.